Interactions of anions and cations in carbon nanotubes - Mohammadzadeh, Leila (2016)
We consider the insertion of alkali-halide ion pairs into a narrow (5,5) car- bon nanotube. In all cases considered, the insertion of a dimer is only slightly exothermic. While the image charge induced on the surface of the tube favors insertion, it simultaneously weakens the Coulomb attraction between the two ions. In addition, the anion experiences a sizable Pauli repulsion. For a one dimensional chain of NaCl embedded in the tube the most favor- able position for the anion is at the center, and for the cation near the wall. The phonon spectrum of such chains shows both an acoustic and an optical branch.